2018
DOI: 10.1073/pnas.1721259115
|View full text |Cite|
|
Sign up to set email alerts
|

Default mode network can support the level of detail in experience during active task states

Abstract: SignificanceAccounts of the default mode network (DMN) as task negative are partly based on evidence for a role of this system in off-task thought. We revisited the evidence for this assumption in a study combining experience sampling with functional neuroimaging. Whether thoughts were related or unrelated to an ongoing task was associated with patterns of neural activity in regions adjacent to unimodal sensorimotor cortex. In contrast, during periods of working-memory maintenance, activity patterns in the DMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
235
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(287 citation statements)
references
References 48 publications
36
235
0
1
Order By: Relevance
“…These observations lead us to speculate that DMN underlies a cognitive process for abstraction of concepts. This interpretation is consistent with findings from several prior studies [48,49]. For example, Spunt et al has shown that conceptualizing the same action at an increasingly higher level of abstraction gives rise to an increasingly greater responses at regions within DMN [49].…”
Section: The Role Of Default-mode Network In Semantic Processingsupporting
confidence: 91%
See 1 more Smart Citation
“…These observations lead us to speculate that DMN underlies a cognitive process for abstraction of concepts. This interpretation is consistent with findings from several prior studies [48,49]. For example, Spunt et al has shown that conceptualizing the same action at an increasingly higher level of abstraction gives rise to an increasingly greater responses at regions within DMN [49].…”
Section: The Role Of Default-mode Network In Semantic Processingsupporting
confidence: 91%
“…Our results suggest that DMN is involved in cortical processing of not only concepts but also semantic relations. This finding underscores the fact that the DMN plays an active role in language and cognition [10,[45][46][47][48], rather than only a task-negative and default mode of brain function [31]. In particular, several semantic relationships, such as "whole-part" and "class-inclusion", are all mapped onto DMN ( Fig.…”
Section: The Role Of Default-mode Network In Semantic Processingmentioning
confidence: 67%
“…While the probes are part of the task and an indication of whether the participant is paying attention, we acknowledge that including them in the analyses may have added some additional confounding elements related to memory and decision‐making processes. Finally, because of the general limitations of the dichotomous nature of collecting MW reports used herein, specific investigation of the brain mechanisms of MW as a function of the content of “off task” reports is beyond the scope or capability of this methodology (Karapanagiotidis et al, ; Sormaz et al, for focus on the content of MW).…”
Section: Discussionmentioning
confidence: 99%
“…Self-generated thoughts that are elaborated in detail and relying on autobiographical memory or deliberate MW processes may be more prominently associated with DN, as revealed by emerging research (Golchert et al, 2017;Sormaz et al, 2018;Spreng et al, 2014;Spreng et al, 2010). Indeed, accumulating evidence has suggested that the link between DN and MW is more complex than initially conceived (e.g., Murphy, Poerio, et al, 2019;Sormaz et al, 2018;Turnbull et al, 2019) and "patterns of activity within the DMN are neither necessary nor sufficient to determine if attention is directed away from the task" (Sormaz et al, 2018, p. 9321).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this view, studies highlight attention and control systems as important in the prioritisation and maintenance of patterns of thought in a context-appropriate manner 14,15 . In contrast, activity patterns within regions allied to the default mode network (DMN), are associated with features of experience that are closely tied to the nature of the representations of the thoughts themselves [16][17][18][19][20] . In healthy participants, for example, changes in activity within the default mode network are linked to patterns of experience with rich subjective details in both episodic memory and working memory tasks contexts.…”
Section: Introductionmentioning
confidence: 99%